Palaeobiology of the early Ediacaran Shuurgat Formation, Zavkhan Terrane, south-western Mongolia. (2nd November 2017) - Anderson, Ross P.; McMahon, Sean; Bold, Uyanga; Macdonald, Francis A.; Briggs, Derek E. G.
Abstract : Early diagenetic chert nodules and small phosphatic clasts in carbonates from the early Ediacaran Shuurgat Formation on the Zavkhan Terrane of south-western Mongolia preserve diverse microfossil communities. Chert nodules contain abundant fragments of organic material, which include organic-walled microfossils and pieces of microbial mats. These fragments are dominated by several Siphonophycus species forming a variety of microbial textures. Spheroids such as Myxococcoides are of secondary importance but dominate one rock sample. Dispersed phosphatic clasts within the carbonate matrix preserve degraded filaments and spheroids. Petrographic characteristics and the composition of the palaeobiological community are similar to those of early Ediacaran assemblages elsewhere. The presence of Salome hubeienesis, previously reported in the Doushantuo Formation of South China and the Krol Group of the Lesser Himalaya, India, and possible multicellular fossils similar to those of Doushantuo, prompts comparisons with the diversity of other biotas, suggesting similarities in regional early Ediacaran communities. The Shuurgat fossils add to the growing evidence for the nature of Ediacaran ecosystems at this critical juncture in Earth history.